The Roof Went First... (Raton, NM Raton Range, 1996)
This article is about first hand accounts of the tornado that hit Cimarron, New Mexico.
Newspaper article + Photograph Electric Company
Mater List Item # 80
File location is in the New Mexico File Cabinets
Keywords: Lee, Kathy; Campanella, Eula -- Cimarron Postmaster; Mora, David; Rogers, Harl -- Mayor of the Village of Cimarron; Cimarron Post Office; Fist Accounts; Tornado Stories; Tornados; Tornado Disasters; Personal Recounts; Bathrooms; Cimarron, New Mexico